Degradation characteristics of γ-ray and proton irradiated 8T CMOS image sensors. (May 2021) - Fu, Jing; Feng, Jie; Li, Yu-Dong; Guo, Qi; Wen, Lin; Zhou, Dong; Zhang, Xiang; Cai, Yu-Long; Liu, Bing-Kai
Abstract: The degradation of a pinned photodiode (PPD) 8T CMOS image sensor (8T-CIS) due to total ionizing dose (TID) and displacement damage dose (DDD) have been investigated with γ-ray and proton irradiation. The dark current and its distributions were studied. We observed a significant increase in the dark current after the proton irradiation than that after the γ-ray irradiation. We observed that the peak values in the Gaussian distribution shift to higher values as a result of TID effects while comparing the dark current distribution results of the γ-ray and proton irradiation. In contrast, the hot pixel tailing increases with the DDD effect. At the same time, the degradation of the light response of the device was investigated by observing the quantum efficiency in the wavelength range of 420–800 nm. A comparison of the results obtained from the γ-ray and proton irradiations showed that the short-wavelength degradation was caused by the TID whereas the DDD caused the degradation in the full spectral range. Highlights: Performance of the 8T pinned CMOS image sensors degraded after irradiation. Dark current increased significantly after proton and γ-ray irradiation. SRIM simulated the proton trajectories and the vacancy density. Distribution of dark current was different after γ-ray and proton irradiation. Light response within 420–800 nm degraded after irradiation.